Percutaneous Endoscopic Gastrostomy in Children - Wael El-Matary (Canadian Journal of Gastroenterology)
Percutaneous endoscopic gastrostomy has been a valuable tool in nutritional rehabilitation since its inception in 1980. Although it was originally described in children, a large sector of the adult population is dependant on it for nutritional support. Percutaneous endoscopic gastrostomy tube insertion is generally a safe procedure. Nevertheless, variable incidence rates of complications have been reported. The present review highlights the up-to-date indications, contraindications and complications of percutaneous endoscopic gastrostomy in children, along with a discussion of issues that need further exploring through future research.